Serological detection and risk factors for equine piroplasmosis in the semiarid region of Pernambuco, northeastern Brazil - de Souza, Eline Almeida Rodrigues; de Carvalho Araujo, Andreina; Pires, Larissa Célly Souza Regis; Freschi, Carla Roberta [UNESP]; Azevedo, Sergio Santos; Machado, Rosangela Zacarias [UNESP]; Horta, Maurício Claudio (FapUNIFESP (SciELO), 2019)
Equine piroplasmosis, an economically important disease in horses, has so far not been reported in Pernambuco state, Brazil. This study aimed to evaluate the seroprevalence of anti-Babesia caballi and anti-Theileria equi antibodies based on the detection of these agents in equine blood and in ticks on horses in the municipality of Petrolina, Pernambuco, northeastern Brazil. Blood samples were drawn from 393 horses and sera were examined by ELISA. The presence of tick infestations was evaluated, and 101 ticks were subjected to DNA amplification for the detection of Babesia spp. by polymerase chain reaction (PCR). No parasites were detected in the blood smears. Anti-B. caballi and anti-T. equi antibodies were found in 27.2% (107/393) and 34.8% (137/393) horses, respectively. Infestation by Dermacentor nitens was detected in 4.3% (17/393) of the horses. There was no DNA amplification of the agents in ticks. The risk factors for the presence of anti-T. equi antibodies (P < 0.05) were: Purebred (P < 0.001), animals older than 156 months (P = 0.014), and the presence of ticks (P = 0.001). No risk factors for B. caballi were identified. This study confirmed the circulation of agents of equine piroplasmosis in the municipality of Petrolina, state of Pernambuco, Brazil.
Detecção sorológica e fatores de riscos para piroplasmose equina na região semiárida de Pernambuco, Nordeste do Brasil
Keywords: Babesia caballi; Diagnostic; ELISA; Horse; PCR; Theileria equi